Morbidity and mortality of 109 consecutive cytoreductive procedures with hyperthermic intraperitoneal chemotherapy (HIPEC) performed at a community hospital - Kerscher, Alexander G.; Mallalieu, Jared; Pitroff, Allison; Kerscher, Friderike; Esquivel, Jesus (World Journal of Surgery, 2010)
Background: Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (HIPEC) is playing an increasing role in the management of isolated peritoneal dissemination of gastrointestinal malignancies. Historically this surgery is associated with a high morbidity and mortality. Recognizing this, our study was developed to prospectively evaluate morbidity and mortality after cytoreductive surgery with HIPEC performed at a community hospital. Methods: From January 19, 2005 to January 9, 2008, 109 consecutive patients successfully underwent cytoreductive surgery with HIPEC for peritoneal surface malignancies. All cases were performed by a single surgeon at a 323-bed community hospital. Using an institutional review board approved study we prospectively evaluated postoperative complications using the standard National Institutes of Health morbidity and mortality grading system. Results: There was no 30-day or inpatient mortality. Overall grade III and IV morbidity was 30.2% (33 of 109 patients); 29.3% of the patients had at least one grade III complication, with the most common being postoperative anemia requiring a blood transfusion in 20 of the 109 patients (18.3%). Eight patients (7.3%) had wound infections, and three patients (2.7%) developed pneumonia. One patient required computerized tomography guided drainage of a pelvic abscess. There were 3 (2.7%) grade IV complications, with only one patient requiring reoperation. Conclusions: Recent studies at tertiary medical centers have shown acceptable morbidity and mortality with this procedure. Our study demonstrates that this procedure can be safely performed in the community setting as well if surgeons, other medical professionals, and ancillary caregivers have great experience in this procedure. © 2009 Société Internationale de Chirurgie.
CRIS-Team Scopus Importer:2025-12-15